Comparative Analysis of the Omics Technologies Used to Study Antimonial, Amphotericin B, and Pentamidine Resistance in Leishmania. (12th May 2014) - Kaur, Gagandeep; Rajput, Bhawana
Abstract : Leishmaniasis is a serious threat in developing countries due to its endemic nature and debilitating symptoms. Extensive research and investigations have been carried out to learn about the mechanism of drug resistance in Leishmania but results obtained in the laboratory are not in agreement with those obtained from the field. Also the lack of knowledge about the mode of action for a number of drugs makes the study of drug resistance more complex. A major concern in recent times has been regarding the role of parasitic virulence in drug resistance for Leishmania . Researchers have employed various techniques to unravel the facts about resistance and virulence in Leishmania . With advent of advanced and more specific means of detection, further hints about probable mechanisms of conferring resistance are expected. This review aims to provide a consolidated picture along with a comparative account of the work done so far to study the mechanism of antimony, amphotericin B, and pentamidine resistance using various techniques.